East African lessons on economic liberalization - Bevan, David; Bigsten, Arne.; Collier, Paul.; Gunning, Jan Willem; Trade Policy Research Centre (Aldershot, Hampshire, U.K. ; Brookfield, Vt., U.S.A. : Gower Pub. ; London : Trade Policy Research Centre, 1987)
This book deals with relations between developed and developing countries in the international trading system whose norm, rules and procedure are set out in general agreement on tariffs and trade (GATT)
Includes bibliographical references: p. [67]
oo 24/09/2018
Loans
Keywords: Commercial Policy; East Africa